The efficacy of Punica granatum extract in the management of recurrent aphthous stomatitis - Parichehr Ghalayani; Behzad Zolfaghary; Ali Reza Farhad; Atefeh Tavangar; Bahram Soleymani (Wolters Kluwer Medknow Publications, 2013)
Objective: Recurrent aphthous stomatitis (RAS) is a common, painful ulcerative disorder of the oral cavity with unknown etiology. No documented cure exists and topical application of medications aims to reduce pain associated with this condition. The aim of this study was to evaluate the efficacy of Punica granatum (PG) extract on the clinical management of RAS. Methods: A total of 40 patients with RAS participated in this randomized, double-blind, and placebo-controlled study. During three episodes of RAS, the efficacy of topical PG gel (10%) was evaluated. Patients were randomly assigned to use placebo gel or PG gel daily. The time of pain elimination and the time of complete healing were recorded and the pain degree was assessed and recorded by each patients in different time intervals including: Before using the oral gel (day 0), and on days 1, 3, 5, 7 after using the product. Data were analyzed using the repeated measures ANOVA, paired and independent t-test. Findings: Mean time of pain elimination showed a significant difference (P < 0.001) between PG group (3.4 ± 1.09) and placebo group (5.9 ± 0.6). The mean duration of complete healing also showed a significant difference (P < 0.001) between PG group (5.3 ± 0.81) and placebo group (8.6 ± 0.99). The visual analog scale score in PG group was significantly less than the placebo group in all time intervals (day 1 to day 7) (P < 0.001). Conclusion: The findings of this study revealed that PG extract in the form of oral gel (10%) may be beneficial in reducing RAS pain and has a positive effect in reducing the overall time period of complete healing. It was concluded that PG is an effective herbal medicine for the management of RAS.